Effects of light stress and light recovery on two maize (Zea mays L.) cultivars - Zhang, Hongyu; Tian, Ping; Mel, Nan; Sui, Pengxiang; Zhang, Wenke; Qi, Hua (Bangladesh Journal of Botany, 2019)
The responses of a density-tolerant (ZD909) and a density-intolerant (DY405) maize cultivar to weak light stress and light recovery were compared. Photosynthetic characteristics and chlorophyll fluorescence parameters were analyzed under three light treatments: natural light (control), 44% shading and 66% shading. The light-saturation point and light-compensation point of both the maize cultivars decreased, whereas the apparent quantum efficiency increased during the shade period and the decreasing degree of light-saturation point and light-compensation point and the increasing degree of apparent quantum efficiency of the ZD909 were both higher than those of DY405. The weak light stress in the spike stage had a greater influence on the photosynthetic characteristics and chlorophyll fluorescence parameters of DY405, which indicated DY405 was less able to adapt to a weak light environment compared with ZD909.